EPIDEMIOLOGI KLINIS DAN DETERMINAN SOSIAL PADA KESELAMATAN PERIOPERATIF: TINJAUAN LITERATUR PENGEMBANGAN MODEL INITIAL ASSESSMENT UNTUK PENCEGAHAN KOMPLIKASI ANESTESI DI RSUD PROVINSI NTB - Elya Endriani; Yuly Peristiowati (Bajang Institute, 2026)
Background: Perioperative safety is a crucial aspect of anesthesiology, yet risk assessments often focus solely on conventional clinical indicators. At RSUD Provinsi NTB, the diverse social profiles of patients necessitate a more comprehensive assessment model. Objective: This study aims to identify the interaction between clinical epidemiology and social determinants of health in influencing perioperative safety and to formulate a basis for developing an Initial Assessment model to prevent anesthesia complications. Methods: This research uses a Systematic Literature Review (SLR) design. Literature searches were conducted through Scopus and Google Scholar databases with a publication range of 2014-2024. Inclusion criteria focused on studies linking clinical and social variables with surgical/anesthetic outcomes. Results: The review findings show that social determinants such as health literacy levels, economic status, and social support have an influence equivalent to clinical comorbidities (such as ASA scores) in predicting perioperative complications. Failure to identify social variables during the initial assessment stage contributes significantly to increased readmission rates and anesthetic adverse events. Conclusion: The development of an Initial Assessment model at RSUD Provinsi NTB must integrate clinical and social parameters to enhance risk detection sensitivity. The implementation of this model is expected to transform anesthesia practice into a more preventive and personalized approach to ensure holistic patient safety.